Opioid Prescription Is Associated With Increased Survival in Older Adult Patients With Pancreatic Cancer in the United States: A Propensity Score Analysis. Issue 5 (6th May 2022) - Zylberberg, Haley M.; Woodrell, Christopher; Rustgi, Sheila D.; Aronson, Anne; Kessel, Elizabeth; Amin, Sunil; Lucas, Aimee L.
Abstract : PURPOSE: Few studies have assessed the interaction between pain treatment and mortality in pancreatic cancer. The aim of this study was to investigate the association between receipt of opioid prescriptions and survival in adults with pancreatic cancer. METHODS: The SEER-Medicare linked database was used to identify patients diagnosed with late-stage pancreatic cancer between 2007 and 2015. Kaplan-Meier models were used to assess the association between opioid prescriptions in the year after cancer diagnosis and survival. Cox proportional hazard models were used to determine the association between opioid receipt and survival, adjusting for propensity score and other relevant confounders including cancer-directed therapies and palliative care referral. RESULTS: A total of 5, 770 older adults with pancreatic cancer were identified; 1, 678 (29.1%) were prescribed opioids for at least 60 days. Median survival was increased in those with opioid prescriptions (6.0 months) compared with those without (4.0 months, P < .0001). After adjustment for confounders, opioid prescriptions were still associated with improved survival (hazard ratio 0.80; 95% CI, 0.75 to 0.86). On multivariable analysis, opioid prescriptions were associated with older age, female sex, residing in nonmetro areas, and treatment with celiac plexus neurolysis, chemotherapy, and radiation. CONCLUSION: Receipt of opioid prescriptions is associated with longer survival in patients with pancreatic cancer. This may be due to the impact of cancer-related pain, although further studies are needed to better understand the interaction between pain management, cancer-directed therapies, and systemic factors, such as palliative care, availability of opioids, and clinical practice culture.